1968
DOI: 10.21273/hortsci.3.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gibberellin A3 on Fruit Shape and Subsequent Seed Dormancy of Apple1

Abstract: Considerable work has been done on the effects of gibberellins on parthenocarpic set and growth of apple fruits. Bukovac (1) has reviewed the literature in this field and has presented further evidence that seedless fruits induced to set by gibberellins A3 and A4 (GA3 and GA4) are distinctly more elongate than normal seeded fruits. More recently Dennis and Edgerton (2) found that GA made seeded fruits of one variety of apple more elongate than controls, although shape was not altered on several other varieties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…These results indicate that the advanced maturity and elongated shape previously noted in parthenocarpic peaches (2,3,4) should not be ascribed to the absence of developing ovules, but rather to the applied GA. The increase in length-diameter ratio of nonparthenocarpic peaches as a result of GA treatment parallels a similar response in apples (6,7).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…These results indicate that the advanced maturity and elongated shape previously noted in parthenocarpic peaches (2,3,4) should not be ascribed to the absence of developing ovules, but rather to the applied GA. The increase in length-diameter ratio of nonparthenocarpic peaches as a result of GA treatment parallels a similar response in apples (6,7).…”
Section: Introductionsupporting
confidence: 57%
“…Gibberellin sprays have been used successfully in Europe to increase fruit-set of pears when the developing ovules were killed by frosts or when pollinating conditions were unsatisfactory (6,8,9,11,12,13). Tests of gibberellin on 'Bartlett' in California indicated limited commercial benefit, coupled with severe inhibition of flowering (4).…”
mentioning
confidence: 99%
“…Sullivan (18) found that the temperature for the first few days after the flowers opened influenced the ultimate shape of the apples. Westwood and Bjornstad (21) reported that gibberellin applications before bloom produced elongated apples. Fisher and Looney (7) found no effect on fruit shape from postbloom Alar sprays, and most reports do not mention any effects of Alar on fruit shape.…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…Fluctuating endogenous hormone levels in the fruit during different growth stages impact fruit shape. The role of hormones in fruit morphology varies, with gibberellins promoting cell elongation and fruit lengthening [16,18]. These phytohormones act both individually and synergistically to regulate plant fruit growth and development.…”
Section: Introductionmentioning
confidence: 99%